The Cult of Celebrity and Trade Marks: the next instalment - Gillian Davies (SCRIPTed: A Journal of Law, Technology & Society, 2004)
In response to the increasing use of registered trade marks by celebrities to protect their names from exploitation, the UK Trade Marks Registry has recently issued guidance on registration of "famous names". This article seeks to examine the implications of the guidance in light of the existing legislative framework for registration of a personal name and recent judicial developments, together with examples of some famous names that have been granted registered protection.